Show Me The Money: Remedies under the Privacy Act - Evans, Katrine (Victoria University of Wellington Law Review, 2005)
This article examines the remedies available for breaches of the Privacy Act 1993. The author first explores the limited range of options available to the Privacy Commissioner, and highlights the success of the low-level approach to resolving cases which is adopted in practice. The Human Rights Review Tribunal has formal remedial powers, including the award of damages and costs. Although a tariff system is not realistic in privacy cases, the Tribunal has given strong guidance on how questions about remedies, including damages, will be decided. The author is of the view that the Tribunal has no jurisdiction to grant punitive damages but that an amendment to the Act to allow for this would be valuable. Parties to complaints need to be aware that formal remedies are rare and remain measures of last resort.